1978
DOI: 10.1007/bf01887100
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic submucosal gastric cysts: Report of two cases, one in association with carcinoma

Abstract: Two cases of heterotopic submucosal gastric cysts, one with a coexisting superficial spreading carcinoma, are described. This is an uncommon entity with which radiologists should be familiar. An association between such cysts and carcinoma has been predicated previously. The induction of submucosal gastric cysts in monkeys fed polychlorinated biphenyls is cited, and the potential significance of this observation with regard to such lesions in humans is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, there has been no report describing the relation of bronchogenic cyst and gastric cancer. An association between gastric diffuse submucosal cysts and gastric cancer has been reported [18][19][20][21][22][23]. Iwanaga et al [19] examined 12 cases of the stomach with submucosal cysts, carcinoma and atypical hyperplasia, and their results showed that erosion or regenerative epithelia were evident on the gastric mucosa of all 12 cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there has been no report describing the relation of bronchogenic cyst and gastric cancer. An association between gastric diffuse submucosal cysts and gastric cancer has been reported [18][19][20][21][22][23]. Iwanaga et al [19] examined 12 cases of the stomach with submucosal cysts, carcinoma and atypical hyperplasia, and their results showed that erosion or regenerative epithelia were evident on the gastric mucosa of all 12 cases.…”
Section: Discussionmentioning
confidence: 95%
“…Pillay et al [20] reported a case of diffuse cystic glandular malformation and adenocarcinoma of the stomach, and in their case variable degrees of acute and chronic inflammatory changes in the mucosa and in the submucosa around the glands were seen. Martel et al [21] reported a case of heterotopic submucosal gastric cysts with adenocarcinoma. In their case, numerous large cysts were evident in the submucosa beneath the adenocarcinoma, and the invasive neoplasm was focally evident adjacent to the cysts; gastric mucosa manifested extensive and diffuse chronic inflammation with lymphocytes and focal intestinalization.…”
Section: Discussionmentioning
confidence: 98%
“…The diffuse heterotopic submucosal cystic malformations (submucosal cysts) of the stomach have been reported under several names, including multiple diffuse cystic disease [1], diffuse submucosal cystic disease [2], diffuse cystic glandular malformation [3], heterotopic gastric glands [6], and heterotopic submucosal gastric cysts [7]. These cysts have been found in stomachs resected for gastric carcinoma, and their possible association with gastric carcinoma has been suggested [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…One describes them as congenital, similar to a hamartoma [1,3,8], and the other regards them as acquired lesions [2,6,7]. The latter theory suggests that gastritis may give rise to these cysts and that the development of heterotopic cysts in the submucosa may make the mucosal surface more prone to repeated erosion regeneration which may result in carcinoma or atypical hyperplasia [2,6,7]. In the present case, the mucosa was dotted with small erosions, the distribution of which corresponded closely to that of the submucosal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain this phenomenon. One possibility is that, in the present case, the tumor may have originated from enterochromaffinlike cells in the heterotopic submucosal gastric gland [16] ; however, it is difficult to determine this. Indeed, there were no diffuse heterotopic submucosal cysts in resected specimens of the second operation.…”
mentioning
confidence: 86%